2015
DOI: 10.1007/s11051-015-2956-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural organic matter on fate and transport of silver nanoparticles in saturated porous media: laboratory experiments and modeling

Abstract: Understanding the fate and transport of silver nanoparticles (AgNPs) is of importance due to their widespread use and potential harmful effects on humans and the environment. The present study investigates the fate and transport of widely used Creighton AgNPs in saturated porous media. Previous investigations of AgNP transport in the presence of natural organic matter (NOM) report contradictory results regarding how the presence of NOM affected the stability and mobility of AgNPs. In this work, a nonreactive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…The first type of detachment typically emerges where the feeding solution into the column inlet is switched from the injecting particle dispersion to the particle-free solution with the same ionic strength and pH (two-phase injection experiments). This is the most common reference to 'detachment' and has been observed for various NP such as NZVI [105,136], carbon nanotubes [172], silica [102], nanoporous silicate [173], and Ag NP [174][175][176] (Table 2). This is also known as re-entrainment and has been observed as dramatically extended BTC tailing which has been observed for a wide variety of colloids [165,167,171,177].…”
Section: Detachmentmentioning
confidence: 84%
“…The first type of detachment typically emerges where the feeding solution into the column inlet is switched from the injecting particle dispersion to the particle-free solution with the same ionic strength and pH (two-phase injection experiments). This is the most common reference to 'detachment' and has been observed for various NP such as NZVI [105,136], carbon nanotubes [172], silica [102], nanoporous silicate [173], and Ag NP [174][175][176] (Table 2). This is also known as re-entrainment and has been observed as dramatically extended BTC tailing which has been observed for a wide variety of colloids [165,167,171,177].…”
Section: Detachmentmentioning
confidence: 84%
“…nanosilver is coated by polymers while the porous medium is not) (Lin et al 2012). A detailed 705 discussion of the transport of nanosilver in porous media is beyond the scope of this review and 706 can be found elsewhere (Flory et al 2013, Goldberg et al 2014, Kanel et al 2015…”
Section: Influencing Factors Of Nanosilver Aggregationmentioning
confidence: 99%
“…Similarly to coating, natural dissolved organic matter (DOM) which attaches on the surface of the ENMs has a stabilizing effect on the ENMs due to which the ENMs are more persistent to aggregation (Gallego-Urrea et al 2014) ( Figure 2). DOM has been shown to cause disaggregation and subsequent decrease in Ag-NP size distribution at concentrations 5 -20 mg/L total organic carbon (TOC) as Suwannee river humic acid (SRHA) and up to 15 mg Ag/L (Fabrega et al 2009;Kanel et al 2015;Metreveli et al 2015). Similarly, the presence of DOM has been shown to have a stabilizing effect on However, there are also contradictory results showing no significant impact of SRHA (2.5 -10 mg TOC/L) on the aggregation state of carbonate-coated Ag-NPs or disaggregation of pre-agglomerated Ag-NPs (Piccapietra et al 2012).…”
Section: Aggregation and Sedimentationmentioning
confidence: 99%